2019
DOI: 10.1016/j.bbmt.2018.12.237
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbiota Transplantation Can Cure Steroid-Refractory Intestinal Graft-Versus-Host Disease

Abstract: Introduction: Severe acute graft-versus-host disease (aGVHD) is characterized by an imbalance of circulating tissue repair factors, with elevated amphiregulin (AREG) and very low (<10 pg/ml) plasma epidermal growth factor (EGF). We hypothesized that giving supplemental EGF, contained in an inexpensive, commercially available drug (urinary-derived human chorionic gonadotropin [hCG], Pregnyl Ò) in addition to standard aGVHD therapy would improve outcomes. Patients and Methods: Twenty-six patients received hCG/EG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…In adult patients, it has been used to treat refractory Clostridium difficile infections and steroid-resistant gut aGvHD, and to eradicate drug-resistant microorganisms. [70][71][72] Bluestone et al reported FMT administration to treat refractory C. difficile infection in three children, using related and unrelated donors via a gastric tube or colonoscopy. No adverse events were reported, but only one achieved remission.…”
Section: The Challenge Of Fecal Microbiota Transplantation In Childrenmentioning
confidence: 99%
“…In adult patients, it has been used to treat refractory Clostridium difficile infections and steroid-resistant gut aGvHD, and to eradicate drug-resistant microorganisms. [70][71][72] Bluestone et al reported FMT administration to treat refractory C. difficile infection in three children, using related and unrelated donors via a gastric tube or colonoscopy. No adverse events were reported, but only one achieved remission.…”
Section: The Challenge Of Fecal Microbiota Transplantation In Childrenmentioning
confidence: 99%
“…Response to treatment was seen within a median of 14 days (range: 3-28), with a median of two FMT (range: 1-7), and a median of 7 days between treatments (range: 2-60). 46,[98][99][100][101][102][103][104][105][106] Infectious complications occurred in 11 patients. Two had sepsis with bacteria not originating from FMT, 102 and one patient developed diarrhea due to Norovirus that was traced to FMT.…”
Section: Can Fecal Microbiota Transplantation Mitigate Prevailing Acumentioning
confidence: 99%
“…In general, in order to consider FMT as an efficacious therapeutic approach for SR GI aGvHD management, an overall response rate of around 60-70%, with a complete response rate of 30-50% should be a desired target, as these rates are achieved with the use of the approved ruxolitinib treatment and in non-randomized FMT studies. 46,[98][99][100][101][102][103][104][105][106]110 As for the antibiotic treatment peri-FMT, if feasible, 24-48 hours prior to FMT, systemic antibiotics should be stopped or replaced by one with less anti-anaerobic activity such as rifaximin for prophylaxis or cefepime for febrile neutropenic treatment. 46,98,99 Microbiome sequencing of donor and patient samples could help interpreting clinical outcomes.…”
Section: Practical Considerations For Fecal Microbiota Transplantatiomentioning
confidence: 99%
“…One week after FMT, the fecal microbial composition of patients with complete response, defined as resolution of all GvHD symptoms 4 weeks after FMT without other interventions to alleviate symptoms, resembled that of the donors. 116 Two more case reports deserve mention: Kaito and colleagues reported a case of refractory gut GvHD treated effectively and safely using FMT with oral capsules, representing the only case to date in the literature. 117 Zhang and colleagues treated a case of post-HSCT diarrhoea in an adult patient with repeated FMTs from two unrelated infants, one with mixed feeding (formula and complementary food) and one exclusively breastfed, leading to an improvement in symptoms.…”
Section: Single Probioticsmentioning
confidence: 99%